Live bacteria found in gastric cancer tumor tissue - Lv, Xiaoqian; Song, Pengxia; Zhang, Nianhua; Guo, Pengbo; Zhang, Rujian; Wang, Haitao; Hong, Longyan; Xu, Rui; Wang, Yu; Lv, Gang; Zhao, Yinghui (Frontiers in Microbiology, 2025)
BackgroundMost research on gastric cancer and microorganisms has focused on Helicobacter pylori as a causative agent and on the relationship between the microbiota and gastric cancer. There is no direct evidence of bacteria in gastric cancer tissues or their relationship with gastric cancer.MethodsGastric cancer tissue samples were collected, and the bacteria within tumor tissues were observed by transmission electron microscopy. The bacteria cultured were stained by Gram Staining and then subjected to High-throughput third-generation full-length 16S rRNA amplicon sequencing. Pure cultures were used to infect AGS gastric cancer cells, followed by protein extraction and Western blotting to detect POF1B protein expression.ResultsThe bacteria were observed in tumor tissues through transmission electron microscopy and had been cultivated under microaerophilic and anaerobic conditions, specifically, then were identified as Propionibacterium acnes (P. acnes), Klebsiella pneumoniae (K. pneumoniae), and Lactobacillus salivarius (L. salivarius). The vacuolation and mortality of AGS cell infected with P. acnes increased (p < 0.05) and the POF1B protein expression upregulated (p < 0.05).ConclusionThe live bacteria, including L. salivarius, P. acnes, and K. pneumoniae, have been found in gastric cancer tumor tissue. P. acnes specifically upregulate the oncogenic protein POF1B expression. The pathway through which this bacterium enters tumor tissue and its role in the tumor microenvironment require further investigation.